Ensaios sobre o impacto do seguro rural na soja produzida no Matopiba - Ferreira, Francisca Ingrid Gouveia (2024)
The set of tests now being reported examines two cases based on the use of the Rural Premium Subsidy Program in soybean-producing municipalities in the Matopiba region. In the first essay, an analysis is carried out on the impact of the Rural Premium Subsidy Program (PSR), on the harvested area and the gross value of soybean production for producers belonging to the Matopiba region between the years 2005 and 2017. To this end, the Difference-in-Differences methods were combined with Propensity Score Matching. In the immediately following study, the impact of the Rural Insurance Premium Subsidy Program – PSR on the harvested area and the quantity of soybeans produced in the Matopiba region is evaluated. In this context, the entropy balancing method was used, using a set of data at the municipal level for the years 2006 and 2017. The results showed that the municipalities that participated in the PSR had larger harvested areas and gross production value in relation to the who did not participate.